Microproteomic Profiling of High‐Grade Squamous Intraepithelial Lesion of the Cervix: Insight into Biological Mechanisms of Dysplasia and New Potential Diagnostic Markers. Issue 1 (23rd August 2018) - Pottier, Charles; Kriegsmann, Mark; Alberts, Deborah; Smargiasso, Nicolas; Baiwir, Dominique; Mazzucchelli, Gabriel; Herfs, Michael; Fresnais, Margaux; Casadonte, Rita; Delvenne, Philippe; De Pauw, Edwin; Longuespée, Rémi
Abstract : Purpose: High‐grade squamous intraepithelial lesion (HSIL) is a known precursor for squamous cell carcinoma of uterine cervix. Although it is known that SILs are associated to infection by human papillomavirus, downstream biological mechanisms are still poorly described. In this study, we compared the microproteomic profile of HSIL to normal tissues: ectocervix (ectoC) and endocervix (endoC). Experimental design: Tissue regions of endoC, ectoC, and HSlL were collected by laser microdissection (3500 cells each) from five patients. Samples were processed and analyzed using our recently developed laser microdissection‐based microproteomic method. Tissues were compared in order to retrieve HSIL's proteomic profile. Potentially interesting proteins for pathology were stained by immunohistochemistry. Results: We identified 3072 proteins among the fifteen samples and 2386 were quantified in at least four out of the five biological replicates of at least one tissue type. We found 236 proteins more abundant in HSIL. Gene ontology enrichments revealed mechanisms of DNA replication and RNA splicing. Despite the squamous nature of HSIL, a common signature between HSIL and endoC could be found. Finally, potential new markers could support diagnosis of dysplasia in SILs. Conclusion and clinical relevance: This microproteomic investigation of HSIL gives insights into the biology of cervical precancerous lesions.